LA EXACERBACION DE LOS ESPIRITUS LIBERALES Y CONSERVADORES FRETE AL CATALANISMO - Colomines i Companys, Agustí (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay examines the relationship between Catalanism and the official policy of the Spanish Restauración, from the time of the Bases de Manresa to the advent of the Second Spanish Republic. Its fundamental thesis presents the Spanish reaction as always already ahead of the Catalan positions, thus configuring a situation that blocked Catalan participation in state politics. Every moderate option was thus preempted, both in Catalonya and in the Spanish State.